Numerical Simulation of RC Beam-Column Joint: Influence of Discrete Crack Modeling on Hysteresis Response - Brihaspati, Brihaspati; Saputra, Ashar; Setiawan, Angga Fajar (Universitas Ibn Khaldun Bogor, 2025)
Understanding the hysteresis behavior of reinforced concrete (RC) beam-column joints with monolithic slabs under cyclic loading is essential for assessing seismic performance. Finite element analysis (FEA) provides a powerful tool for such studies, but accurately capturing cyclic response remains challenging. This research aims to develop and validate an FEA model that provides the hysteresis behavior of an RC beam-column joint focusing on material modeling approaches and emphasizing the influence of discrete crack modeling in simulating major crack opening and closure. The numerical model is implemented in ABAQUS/Standard, combining the Concrete Damaged Plasticity (CDP) model for concrete, combined hardening for reinforcement, and discrete crack representation to enhance crack behavior simulation. The model is validated against previous experimental results by Durrani & Zerbe (1987) under the same cyclic loading protocol. The results show that least one discrete crack significantly enhances the agreement between numerical and experimental hysteresis loops, while two discrete cracks provide the best match for capturing pinching effect and cyclic stiffness degradation. The compression stiffness recovery parameter (wc) in CDP and the combined hardening model for reinforcement also play critical roles in influencing numerical results. The model successfully reproduces cyclic stiffness degradation and energy dissipation, although minor discrepancies exist due to material data limitations. This study advances numerical modeling of RC beam-column joints under cyclic loading, emphasizing the importance of discrete crack modeling in enhancing simulation accuracy for seismic performance assessment.